Electronic Health Literacy Among Baby Boomers: A Typology - Lynn Sudbury-Riley; Mary FitzPatrick; Peter J. Schulz; Alexandra Hess (SLACK Incorporated, 2024)
Background: Forecasts suggest that older adults will place unprecedented demands on future health care systems. Electronic health (eHealth) resources can potentially mitigate some pressures, but to be effective patients need to be able to use them. The negative relationship between eHealth literacy and age usually results in older adults classified as one homogenous mass, which misses the opportunity to tailor interventions. Objective: This research examines similarities and differences within the baby boom cohort among a sample that uses the internet for health information. Methods: We used an electronic survey with random samples of baby boomers (N = 996) from the United States, the United Kingdom, and New Zealand. Key Results: Four distinct subgroups, or segments, emerged. While not different from a socioeconomic perspective, these four groups have very different levels of eHealth literacy and corresponding health behaviors. Therefore, we contribute a more complex picture than is usually presented in eHealth studies. Conclusions: Resulting insights offer a useful starting point for providers wishing to better tailor health products, services, and communications to this large cohort of future older individuals. [HLRP: Health Literacy Research and Practice. 2024;8(1):e3-e11.]